Cryoturbation in the Central Brooks Range, Alaska. Issue 5 (5th September 2013) - Jelinski, Nicolas A.
Abstract : Cryoturbation in permafrost‐affected soils is important to many Arctic biogeochemical processes and critical to the appropriate classification of Gelisols. Standardized methodologies for describing the soils formed from these processes and knowledge regarding the time scales at which they operate continue to evolve. Twenty‐six profiles were described across a transect in the Midas Lake region of the Central Brooks Range of Alaska using a modified version of the standard USDA and Turbel description protocol that is appropriate for work in wilderness areas. Profile descriptions and associated field data were aggregated and generalized to reveal major trends and relationships in horizonation between cryoturbated and noncryoturbated soils on the transect. A conceptual model for the geomorphic relationships of cryoturbated and noncryoturbated soils on this landscape was developed. In addition to a landscape‐scale perspective, individual profiles were described on patterned ground features at a location where cryoturbated horizons were strongly expressed. Samples from these profiles were analyzed for cesium‐137 ( 137 Cs) activity, and it was found that the surficial activity of this fallout radioisotope varied strongly by material type and position on the patterned ground microtopography. These differences suggest that the use of fallout isotopes, such as 137 Cs, when combined with quantitative profile descriptions and a standardized description protocol, may significantly improve our understanding of the spatial distribution and mechanisms of cryoturbation.